O patrimônio fotográfico da Faculdade de Ciências Políticas e Econômicas do Rio Grande (1955-1972): descrição arquivística e preservação da memória - Simões, Greta Dotto (2022)
The Faculty of Political and Economic Sciences (FCPE), the second higher education unit in the Municipality of Rio Grande, was created in 1955 by the municipal government with the aim of providing higher education in Political and Economic Sciences and housed the Economic Sciences Course and the Commercial Technical College Fernando Freire. The Faculty operated effectively from 1959 to 1972, and in 1969 it was incorporated into the Federal University of Rio Grande (FURG), due to the change in the country's educational system caused by the University Reform. During the development of its activities and functions, the FCPE was responsible for the production and formation of an important documentary collection, which constitutes its Documentary Fund, guarded by the General Archive Coordination. In this work, the photographs that are considered evidence of facts and sources of information of the administrative and teaching activities carried out by the Faculty stand out. Thus, the present research has as general objective to promote the archival description in the photographic collection of the Faculty of Political and Economic Sciences of Rio Grande, from 1955 to 1972, according to the norms and recommendations found in the archival literature, aiming at the preservation of cultural heritage, documentary and institutional memory. The research is classified as exploratory, qualitative and descriptive. Data collection was carried out through direct observation, bibliographic and documentary research. The work addresses the archival function of document description and the description standards recommended for use in archives. Next, an analysis of the context and content of the FCPE photographic collection is presented, providing an interpretation and description to researchers. The description of the photographs was based on the Brazilian Standard for Archival Description, and resulted in the elaboration of the "Selective Catalog of Photographs of FCPE", the final product of the master's dissertation. The production and propagation of the research contributes to the preservation, access and spread of the photographic heritage that portrays the history and memory of one of the Faculties that gave rise to FURG.